Oral health conditions and self-perception among edentulous individuals with different prosthetic status - Maria Madalena Canuto Lemos; Luciane Zanin; Maria Letícia Ramos Jorge; Flávia Martão Flório (Universidade Estadual de Campinas, 2015)
Aim: To evaluate the objective oral health conditions and self-perception of edentulous individuals wearing functional complete dentures (FCD) and non-functional complete dentures (NFCD) and completely edentulous non-denture wearers, and identify the factors that influence self-evaluation and the impact on quality of life. Methods: The convenience sample was selected at the integrated clinic of a Dentistry Course (n=193) and was divided into 3 groups: FCD wearers (n= 54); NFCD wearers (n= 65); 3- edentulous non-denture wearers (n= 74). Data collection was performed by means of interviews, application of the Geriatric Oral Health Assessment Index (GOHAI) and clinical exams. Data were submitted to univariate analysis and logistic regression, considering dichotomization of the sample by the median value of GOHAI (=30). Results: Individuals with NFCD are 4.5 times more likely to show a low GOHAI score than individuals with FCD; edentulous individuals are 7.5 times more likely to show a low GOHAI score than individuals with FCD; individuals that consider their oral health as regular, poor or bad are 3.1 times more likely to show a low GOHAI score than individuals who consider their oral health as good or excellent. Conclusions: Being completely edentulous or wearing NFCD, and having oral health classified as regular, poor or extremely bad were important features for a negative self-perception of oral health, with impact on quality of life.